A VALIDATED ANALYTICAL METHOD FOR THE SIMULTANEOUS ESTIMATION OF CYTARABINE AND DAUNORUBICIN IN BULK AND INFUSION FORMULATION BY REVERSE PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - PRASANTHI CHENGALVA; LATHA LAVANYA PEDDAVENGARI; MADHAVI KUCHANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The novel liposomal infusion formulation of cytarabine and daunorubicin liposomal infusion is considered as new hope in acute myeloid leukemia treatment. The objective of the present study is to develop and validate a simple, rapid, accurate, precise and sensitive reverse-phase high-performance liquid chromatographic (RP-HPLC) method for the simultaneous estimation of cytarabine and daunorubicin in bulk and infusion formulation. Methods: The chromatographic separation of the drugs was achieved on Denali C18 (250 mm×4.6 mm, 5 μm) in isocratic mode with mobile phase consisting of water (pH was adjusted to 3):acetonitrile in the ratio of 55:45 with a flow rate of 1 ml/min at a detection wavelength of 240 nm using photodiode array (PDA) detector. The column temperature was set at 30°C with 10 μl injection volume. The proposed method was validated as per the International council for Harmonisation (ICH) guidelines. Results: The retention times for cytarabine and daunorubicin were found to be 2.323±0.12 min and 3.140±0.16 min, respectively. Linearity (r2=0.999) was observed over a concentration range of 16.2–97.5 μg/ml for cytarabine and 7.2–43.5 μg/ml for daunorubicin. The percentage relative standard deviation (RSD) for precision studies was found to be 0.2 for both the drugs. Conclusion: A simple, rapid, economic, accurate, and precise RP-HPLC method was developed for simultaneous quantitative estimation of cytarabine and daunorubicin, and the method was validated as per the ICH guidelines. Hence, the method can be employed for the routine analysis of cytarabine and daunorubicin in bulk and infusion formulation.